THE IMPACT OF AI-POWERED TOOLS (CHAT GPT) ON ENGLISH LANGUAGE LEARNING IN EFL CLASSROOMS: A CASE STUDY IN UZBEKISTAN (Ustozlar uchun, 2026)
The rapid advancement of artificial intelligence has introduced new paradigms in English as a Foreign Language (EFL) education. This study investigates the impact of AI-powered tools, particularly Chat GPT, on the English language learning outcomes of university-level EFL students in Uzbekistan. Using a mixed-methods approach, 60 students were divided into a control group (traditional instruction) and an experimental group (AI-assisted instruction) over one semester. Pre- and post-test scores, classroom observations, and structured interviews were employed as data collection instruments. The results revealed statistically significant improvements in writing proficiency (p < 0.05) and vocabulary acquisition among the experimental group. Students reported higher levels of motivation and autonomy when using ChatGPT as a learning assistant. However, concerns regarding academic integrity and over-reliance on AI were also identified. These findings suggest that integrating AI tools into EFL classrooms can enhance language learning, provided that clear pedagogical frameworks and ethical guidelines are established.